Abon Merapi (Mente Rasa Sapi) sebagai Bukti Kecintaan terhadap Kearifan Lokal Masyarakat Lombok Timur - Anwar, Evi Kurniawati; Maenun, Maenun; Saniah, Saniah; Sari, Linda Purnama; Rahmah, Pisyahri; Safnowandi, Safnowandi; Karmana, I Wayan (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2024)
Cashew nuts (Anacardium occidentale) are plants with great potential and high economic value in West Nusa Tenggara Province. East Lombok Regency is one of the cashew producing areas in Indonesia. Local people usually call it guava jemet or guava jebet. So far, cashew farming communities have only used the true fruit or what is better known as the seeds for sale. However, in reality, the pseudo-fruit of cashew nuts or what is commonly referred to as the fruit can be processed into a product that has high economic value, namely made into shredded meat. Shredded cashew is usually made from cashew fruit that is quite old or already ripe. Thus, the aim of making cashew floss is to create a new innovative product by optimizing the use of cashew fruit as an ingredient for making shredded cashew fruit, so that it can produce cashew floss with good quality and high selling value and is beneficial for consumers. This method of making shredded meat starts from the tool and material preparation stage, the processing stage, the shredded making stage, and the evaluation stage. Then a report is prepared and the article is published. It is hoped that the results of this activity will become an innovative product with high sales value and be published as an article that can be used as a reference for optimizing natural resources.